2020
DOI: 10.1200/jco.2020.38.4_suppl.364
|View full text |Cite
|
Sign up to set email alerts
|

Refusal of surgery results in inferior survival in esophageal cancer.

Abstract: 364 Background: Trimodality therapy with chemoradiation followed by surgery is the standard of care for non-metastatic esophageal cancer. Some patients refuse surgery and this information is captured in the National Cancer Database (NCDB). We sought to understand factors associated with refusal of surgery in these patients and to compare their survival rates with those who undergo surgery. Methods: Data from the NCDB for patients with pathologically proven non-metastatic esophageal cancer from 2006 to 2013 we… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
4
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(6 citation statements)
references
References 0 publications
2
4
0
Order By: Relevance
“…Regarding distance from patient to provider, our findings are in agreement with a prior report on stage I–III rectal cancer, which reported increased surgery receipt in individuals who lived further from their provider’s location [ 22 ]. Our findings also are in agreement with a previous study on esophageal cancer that reported increased odds of surgery receipt with increased patient to provider distance [ 16 ]. Additionally, our findings revealed that surgery receipt was associated with receiving care at an academic facility, which is consistent with prior studies in individuals with esophageal and oral cavity cancer [ 16 , 18 ].…”
Section: Discussionsupporting
confidence: 93%
See 4 more Smart Citations
“…Regarding distance from patient to provider, our findings are in agreement with a prior report on stage I–III rectal cancer, which reported increased surgery receipt in individuals who lived further from their provider’s location [ 22 ]. Our findings also are in agreement with a previous study on esophageal cancer that reported increased odds of surgery receipt with increased patient to provider distance [ 16 ]. Additionally, our findings revealed that surgery receipt was associated with receiving care at an academic facility, which is consistent with prior studies in individuals with esophageal and oral cavity cancer [ 16 , 18 ].…”
Section: Discussionsupporting
confidence: 93%
“…Many sociodemographic factors have been previously reported as predictors of surgery refusal in patients with various cancers. For example, advanced age as a predictor of surgery refusal has been well documented in various malignant tumors, including breast cancer, esophageal cancer, colon cancer, HSNCC, and oral cavity cancer [ 11 , 12 , 14 , 16 , 18 ]. African American race is another sociodemographic factor associated with increased risk of surgery refusal in prostate cancer, colon cancer, HNSCC, laryngeal cancer, and hepatocellular carcinoma [ 12 , 14 , 15 , 19 , 20 ].…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations